Impact of Emergent Cervical Carotid Stenting in Tandem Occlusion Strokes Treated by Thrombectomy: A Review of the TITAN Collaboration - Zhu, François; Bracard, Serge; Anxionnat, René; Derelle, Anne-Laure; Tonnelet, Romain; Liao, Liang; Mione, Gioia; Humbertjean, Lisa; Lacour, Jean-Christophe; Hossu, Gabriela; Anadani, Mohammad; Richard, Sébastien; et al. (Frontiers in Neurology, 2019)
Introduction-Endovascular therapy has been shown to be an effective and safe treatment for tandem occlusion. The endovascular therapeutic strategies for tandem occlusions strokes have not been adequately evaluated and the best approach is still controversial. The TITAN (Thrombectomy in TANdem occlusions) registry was a result of a collaborative effort to identify the best therapeutic approach for acute ischemic stroke due to tandem lesion. In this review, we aim to summarize the main findings of the TITAN study and discuss the challenges of treatment for tandem occlusion in the era of endovascular thrombectomy. Methods-A review of the data from the multicenter international observational and non-randomized TITAN registry was performed. The TITAN registry included acute ischemic stroke patients with tandem lesions (proximal intracranial occlusion and cervical carotid artery occlusion or stenosis>90%) who were treated with thrombectomy with or without carotid artery stenting. Results-Prior intravenous thrombolysis and emergent cervical carotid stenting were associated with higher reperfusion (mTICI 2b-3 and mTICI 3) rates at the end of the intervention. Poor outcome did not occur more frequently after stenting than after conservative treatment of the cervical carotid lesion. Emergent carotid stenting with antithrombotic agents and intracranial thrombectomy yielded higher reperfusion rate and good outcome (90-day mRS 0-2) compared to other strategies (carotid artery stenting and thrombectomy without antithrombotic, angioplasty and thrombectomy, or thrombectomy alone). Pretreatment intravenous thrombolysis was not associated with increased risk of hemorrhagic complications. Likewise, periprocedural unfractionated heparin did not modify the efficacy and safety results. Etiology of carotid artery lesion (atherosclerosis versus dissection) did not emerge as predictor of outcome or recanalization. Conclusion-Emergent stenting of the cervical carotid lesion with antithrombotic agents in conjunction to thrombectomy appears to be the best treatment strategy for acute ischemic strokes with tandem lesions. These findings will be further investigated in the ongoing randomized controlled TITAN trial.